Speaking Anxiety in Secondary School ( A Case Study in Junior High School ) - Putri Sazhikirani Saharani; Nurfaizah Sahib; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
The aim of this study was to find out there was a factor that made students’ anxiety in speaking English after doing the research in VIII-8 class at SMPN 24Makassar in the 2022/2023 academic year. The approach of this study was qualitative descriptive research with using questionnaire public speaking class anxiety scale. Students’ speaking anxiety was filled by used questionnaire to electing the data. The writer took the eighth grade with 27 students from the population. The method of this study used purposive sampling technique to select a sample from the population. The results of data analysis showed that there was a factor that made students’ anxiety in speaking. The score obtained from factor of embarrassment was 225. In all factors it showed that the number of embarrassment was the highest. Factor of lack of preparation score was 55. It showed that in all factors the number of lack of preparation was lowest from the all factors. It means that factor embarrassment was the most factors that made students’ anxiety in speaking English at eighth grade students at SMPN 24 Makassar.